2010
DOI: 10.1016/j.jbiomech.2010.05.013
|View full text |Cite
|
Sign up to set email alerts
|

In vivo cartilage contact strains in patients with lateral ankle instability

Abstract: Damage to the anterior talofibular ligament (ATFL) and cacaneofibular ligament (CFL) during ankle sprain may be linked to the development of osteoarthritis. Altered tibiotalar kinematics have been demonstrated in these patients, but the effects of lateral ankle instability (LAI) on in vivo cartilage strains have not been described. We hypothesized that peak cartilage strains increase, and the location is shifted in patients with ATFL injuries. We used 3-D MRI models and biplanar fluoroscopy to evaluate in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(116 citation statements)
references
References 48 publications
4
111
1
Order By: Relevance
“…The present results can be explained by those of previous studies. Bischof et al 33 reported that patients with ATFL injuries showed increased and anteromedially shifted peak cartilage contact strain using MRI and orthogonal fluoroscopy to determine the in vivo cartilage contact strains. Caputo et al 34 reported altered anterior translation, internal rotation, and superior translation of the talus relative to the tibia in ATFL-deficient ankles using in vivo kinematic measurements of the tibiotalar joint.…”
Section: Discussionmentioning
confidence: 99%
“…The present results can be explained by those of previous studies. Bischof et al 33 reported that patients with ATFL injuries showed increased and anteromedially shifted peak cartilage contact strain using MRI and orthogonal fluoroscopy to determine the in vivo cartilage contact strains. Caputo et al 34 reported altered anterior translation, internal rotation, and superior translation of the talus relative to the tibia in ATFL-deficient ankles using in vivo kinematic measurements of the tibiotalar joint.…”
Section: Discussionmentioning
confidence: 99%
“…If the initial LAS is an underlying cause of osteochondral lesions, recurrent LASs and episodes of giving way likely exacerbate contact stress adaptations,52 further advancing degenerative changes. While speculative, this would place a premium on restoring appropriate biomechanics and motor control following an LAS in order to mitigate cartilage degeneration.…”
Section: Section B: Mid-term and Long-term Consequences Of Lassmentioning
confidence: 99%
“…Patients may have a subjective sense of instability where an innocuous misstep may lead to another ankle injury [8]. Recurrent ankle sprains may alter the biomechanics at the ankle joint which can potentially lead to cartilage degeneration over time [9][10][11][12][13]. Up to 93% of patients with ankle instability have associated intra-articular pathology [14][15][16].…”
Section: Introductionmentioning
confidence: 99%